Sailing together: challenges for an inclusive team of visually impaired and sighted athletes at Kiel Week - Greve, S.; Bükers, F.; Bodenstedt, P.; Steinvoord, K.; Krieger, C. (Frontiers in Sports and Active Living, 2025)
The BAT-Sailing project is a joint project of the Norddeutscher Regatta Verein and FC St. Pauli Segeln, which enables people with and without disabilities to pursue sailing together in a performance-oriented manner as part of training and regattas. The project originally started with the intention of realizing the joint sailing of sighted and blind athletes. This article presents the scientific monitoring that was carried out at the request of the BAT Sailing Team in order to scrutinize and optimize the practice of the BAT Sailing Team [The name is derived from the word "bat" and alludes the symbolic transfer: cannot see (well) but can fly (or sail)]. The evaluation was carried out according to the Patton approach of a utilization-focused evaluation, which places the needs and values of the users at the center of the evaluation. The evaluation took place over three consecutive years (2021, 2022, 2023) and included interviews with the athletes, coaches and organizers of the BAT Sailing Team. The results showed that communication between sighted and blind athletes plays a special role and that the athletes learn to understand and support each other. Within the process of the evaluation it was able to identify communication as a strength that has developed in the joint sailing of people with and without visual impairments and that benefits above all people without disabilities. The results of the evaluation show that the utilization-focused evaluation is an effective tool for improving the practice of an inclusive sailing team that wants to act in a performance-oriented manner but also wants to ensure the participation of all potentially interested parties, regardless of their dis/abilities. The results of the evaluation can also be transferred to other inclusive sports projects that face a similar challenge.